Magnesium and iron oxides influence on sintering processes and phase formation of anorthite ceramics based on natural raw materials; Известия высших учебных заведений. Серия: Химия и химическая технология; Т. 67, вып. 4 - Sharafeev Sh. M. Sharif Mnirovich (Chemical technology, 2024)
Заглавие с экрана